Application of Guided Inquiry Model Outdoor Learning to Improve Learning Motivation and Conceptual Understanding in Global Warming Material - Fadhilatul Mubarokah; Firdaus Firdaus; Maryono Maryono (JPF (Jurnal Pendidikan Fisika) Universitas Islam Negeri Alauddin Makassar, 2024)
This research aims to: 1) To determine the differences in students' learning motivation and understanding of concepts in global warming material between learning that uses a guided inquiry model through outdoor learning and learning that takes place conventionally. 2) To determine the magnitude of the increase in learning motivation and understanding of concepts in global warming material between learning that uses a guided inquiry model through outdoor learning and learning that takes place conventionally. This research includes research with a quantitative approach. The method used is Quasi Experimental Design. This research used a pretest-posttest with two groups, namely the experimental group and the control group. Data analysis techniques use preliminary tests of normality, homogeneity, and use hypothesis analysis with the T test and Gain test assisted by SPSS.24. The results of this research show that: 1) In the first follow-up test, namely the t test on students' conceptual understanding data, a significance value of 0.00 < 0.05 was obtained, so that Ha was accepted and H0 was rejected. For learning motivation data, a significance value of 0.00 <0.05 was obtained, so that Ha was accepted and H0 was rejected. It can be concluded that there are significant differences in students' conceptual understanding and learning motivation. 2) There is an increase in understanding of concepts with an average N-Gain score in the experimental class of 64.657 or 64.6% with medium criteria, while in the control class it is 27.32 or 27% with low criteria. The N-Gain calculation of learning motivation for the experimental class received a score of 68.550 or 68.5% with medium criteria, while for the control class it was 3.96 or 3% with low criteria. From these results it can be concluded that the guided inquiry model through outdoor learning is effective in increasing students' learning motivation and understanding of concepts in global warming material compared to conventional learning.